The prospect for design of eco-tourism areas: Meeting the needs of the visitors while maintaining sustainability - Yaman, Maheran; Nik Abdul rahman, Nuik Ismail azlan (IIUM, 2009)
ABSTRACT The range of issues and prospects associated with the design of eco-tourism areas is discussed in this paper based from literature reviews, case studies and standard practices by designers and local inhabitants. It draws attention to the need for sustainability in design in relation to technology selection and aesthetic qualities. Absolute design criteria based on technical expertise without regard to sustainability should be reviewed. The ethics of selectively transferring design expertise from the drawing board into the ground should be reviewed. This paper will try to provide some aspect of holistic design of eco-tourism areas to serve the needs of the visitors and preserving the sustainability of the natural areas.